Strategy for de-commoditizing a commodity: focusing on replacement filters - Smith, Nate (Kansas State University, 2011)
Creating product differentiation as it pertains to a commodity is a difficult undertaking. Products defined as a commodity in the market place are typically very similar in nature and allocating marketing funds to execute the four P’s of traditional marketing: Product, Promotion, Price, and Placement can be a daunting task that may provide little to no economic reward. The goal in marketing a product that is thought of as a commodity is to reduce the amount of waste in capital and labor, while at the same time extracting as much profit as possible in the targeted market. It is extremely important for the firm to know the market for which it competes. Pricing is usually the primary factor that goes into the purchasing decision of a commodity; therefore the commodity must be priced competitively within the target market. To achieve a positive margin between the perceived market value of the commodity and the price for which the firm is commanding, the company must focus on two areas of marketing. First, the critical value factors must be perceived more valuable for the product the firm is attempting to sell in the market place than that of the competition. Second, a preeminent distribution channel must be in place to adapt to the ever changing nuances of the market. Availability of the commodity is critical because potential customers can easily find another source for a like product. This thesis analyzes the agricultural replacement filter business and provides recommendations to the firm, in this case John Deere Company, on how to capture business from owners of John Deere equipment that currently purchase replacement filters from another source besides John Deere. The study begins by taking a look at the filter business from a macro level to understand the broader market, and then drills down to the variables that drive the purchasing decision of the customer. The results indicate that price is the number one reason why potential John Deere filter customers conduct business with non-John Deere sources. However, based on deeper analysis, into the factors that drive customers away from the John Deere distribution channel, a strategy is provided to add business by increasing the value of the John Deere filter for the consumer that will in turn increase revenue for the firm. The agricultural machinery business is a highly competitive industry. Similar to most industries, there is increasing customer and distribution consolidation within this market. This in turn increases the value of each producer. The primary distribution channel for agricultural equipment, mainly OEM dealers (original equipment manufacturers) ‘seeds’ rural North America with complete goods such as tractors and combines that producers use to work the land. However, the equipment must be maintained with service parts for the machine to operate productively and efficiently. The service parts the distribution channel sells to end-users are also extremely competitive because of the many products available. Machine filters such as fuel, air, and engine oil are service parts that end-users must systematically replace to keep their machines running efficiently when their equipment is in use. Filters that have surpassed their service life-cycle inhibit the performance of the machine, eventually causing the customer expensive down time. Filters, as well as other maintenance parts that are consumable, are an expense many operators look to minimize to increase their net profit. Therefore, many producers will try to find the best deal when replacing filters. The assumption of the author is that customers base their purchasing decision on the price of the product versus other factors such as quality, availability, or brand loyalty.
Keywords: Filters; John; Deere; Pricing; Finance; Strategy